2020
DOI: 10.12998/wjcc.v8.i15.3259
|View full text |Cite
|
Sign up to set email alerts
|

Dydrogesterone treatment for menstrual-cycle regularization in abnormal uterine bleeding – ovulation dysfunction patients

Abstract: BACKGROUND Dydrogesterone has shown significant efficacy in treatment of irregular menstrual cycle due to abnormal uterine bleeding - ovulation dysfunction (AUB-O), but there were few relevant studies. This observational study was designed to evaluate the effectiveness of dydrogesterone for the treatment of Chinese patients with AUB-O. AIM To evaluate the effects of dydrogesterone on menstrual-cycle (MC) regularization and metabolism in the patients with AUB-O. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…There is a lack of evidence from randomized controlled trials, especially about the effect of treatment for AUB-O on endometrial histopathology. Most studies showed only intermediate outcomes, such as menstrual cycle regularization 15 17 . Our present study showed that two cyclic-progestin regimens (DSG 150 µg/d or MPA 10 mg/d, 10 d/month) could transform endometrium to complete pseudodecidualization in > 70% of cases in the treatment cycle-1 and could normalize menstruation in > 90% of all treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of evidence from randomized controlled trials, especially about the effect of treatment for AUB-O on endometrial histopathology. Most studies showed only intermediate outcomes, such as menstrual cycle regularization 15 17 . Our present study showed that two cyclic-progestin regimens (DSG 150 µg/d or MPA 10 mg/d, 10 d/month) could transform endometrium to complete pseudodecidualization in > 70% of cases in the treatment cycle-1 and could normalize menstruation in > 90% of all treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Dydrogesterone's effectiveness for menstrual cycle regulation has been reported to be equal to other orally administered progestins like Norethisterone, on eliciting secretory phase activity. 17 But these above-mentioned studies were done on the international level and no local studies have been found to compare the effectiveness of the two hormones for menstrual cycle regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Затримка або відсутність овуляції, СПКЯ, призводить до нестачі прогестерону і надмірного виробництва простагландину E 2 з фолікулів яєчників, викликаючи проліферацію ендометрія і схильність до непередбачуваних менструальних кровотеч [3]. Дефіцит прогестерону і безперешкодна секреція естрогенів призводять до стійкої проліферації ендометрія й індукції виділень, що викликає АМК-O [13].…”
Section: етіопатогенезunclassified